Análise da influência das condições de processamento na morfologia e nas propriedades de blendas poliméricas PBT/ABS moldadas por injeção - Cardinali, Daniel Albuquerque (2011)
A study on the correlation of blend morphology, properties, the injection molding process and manufacturing methods of polymeric blends constituted of PBT and ABS was proposed. Thus, uncompatibilized PBT/ABS blends have been prepared in a twin-screw extruder using different parameters of process, in order to obtain blends presenting distinct properties and, if possible, distinct morphologies. The extruded blends have been eventually submitted to the injection molding process for the evaluation of the influence of the injection molding process parameters on the morphology, thermal properties and mechanical properties, especially impact strength, of PBT/ABS blends. The following parameters of the injection molding process and its influence on the properties mentioned above have been studied: injection temperature, mold temperature, holding pressure and injection speed. The Design of Experiments approach has been used to arrange the full set of experiments and also to statistically analyze the results. The morphology of the extruded and injection molded blends has been investigated by Transmission Electron Microscopy, the mechanical properties by Izod impact strength tests and the degradation of the blends constituents has also been evaluated. The results have indicated that major differences on the impact strength of the samples can be achieved by only varying the injection molding parameters. Furthermore, mold temperature and injection speed have significantly affected the impact strength and the ductile-brittle transition temperature of the injection molded samples. Morphological analyses and degradation studies have suggested that the dispersion degree of the ABS disperse phase particles within the PBT matrix plays an essential role in determining the impact strength of the blends.